La crítica y sus fundamentos a partir de la perspectiva de George Lukács - Gambarotta, Emiliano Matías (2011)
This paper analyses the George Lukács’s perspective developed in his History and class conscience, with the main objective of doing an appropriation of those methodical and conceptual elements, which are particularly productive for a critical theory of the late-modern society. For that reason, this article investigates the methodical and epistemic function that the notion of totality has in the lukacsianan’s dialectical point of view. This is done asking what makes possible an analytic distinction between two different conceptions of the subject-object relationship from the totality’s point of view, both of them overlap in his thought, without any dissociation. Each one of these conceptions implies a different way of understanding the particular entwinement between the objective social structure and the subject’s mode of thought and action. And this impacts in the complete methodical structuration of the critical perspective. Based on this problematic the paper studies a second objective: to grasp a blind point, that generated by the (double) rejection of the perspectives that based on a normative reason, as well as the ones that leave it without any fundament.